Development of the White Lessi Beach Tourist Attraction as a Source of Income for the Residents of Kulur Village, Saparua District, Central Maluku Regency - Fatma Pelupessy; Melianus Salakory; Ferdinand Salomo Leuwol (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study aims to analyze the development of the White Lessi Beach tourist attraction as a source of income for the residents of Kulur Village, Saparua District, Central Maluku Regency. The beach holds great potential as a premier tourist destination due to its pristine natural beauty. However, suboptimal management and infrastructure, such as poor road access and limited supporting facilities, are major obstacles to its development. This research employs a qualitative method, with data collection techniques including interviews, observations, and questionnaires. The results indicate that improving infrastructure, expanding promotion, and actively involving the local community in tourism management are key factors supporting the development of White Lessi Beach. Based on the SWOT analysis, enhancing tourism facilities and improving accessibility are expected to boost tourist attraction. In conclusion, with proper management strategies and strong collaboration between the government, community, and businesses, White Lessi Beach has the potential to become a significant source of income for the local population.